Film, history and cultural memory: cinematic representations of Vietnam-era America during the culture wars, 1987-1995 - Burton, James Amos (2008)
My thesis is intended as an intellectual opportunity to take what, I argue, are the "dead ends" of work on the history film in a new direction. I examine cinematic representations of the Vietnam War-era America (1964-1974) produced during the "hot" culture wars (1987-1995). I argue that disagreements among historians and commentators concerning the (mis)representation of history on screen are stymied by either an over-emphasis on factual infidelity, or by dismissal of such concerns as irrelevant. In contradistinction to such approaches, I analyse this group of films in the context of a fluid and negotiated cultural memory. I argue that the consumption of popular films becomes part of a vast intertextual mosaic of remembering and forgetting that is constantly redefining, and reimagining, the past. Representations of history in popular film affect the industrial construction of cultural memory, but Hollywood's intertextual relay of promotion and accompanying wider media discourses also contributes to a climate in which film impacts upon collective memory. I analyse the films firmly within the discursive moment of their production (the culture wars), the circulating promotional discourses that accompany them, and the always already circulating notions of their subjects.